Uporabnost zbirk prostorskih podatkov in njihove kartografske upodobitve za potrebe obdavčitve nepremičnin - Starček, Simon (visokošolska dela, 2017)
The present PhD thesis discusses spatial data related to property taxation as well as their cartographic representations, which are designated for all participants in the process of property taxation, namely, lay public, policies and professional grounds planners and decision makers. The field of property taxation is discussed according to our own methodological approach based on the research of the properties of the taxation system and considering the demands of the contemporary property taxation system and the constitution principles. Based on the above-mentioned the property taxation system in some countries of the world and in Slovenia has been studied in detail with the emphasis on the analysis of the charge for use of the building ground and property taxation as in compliance with The Real Property Tax Act (2013). According to our designed methodological approach, an analysis of quality of the Real Property Register has been conducted with regard to all elements of quality as defined by the international, European and Slovenian standard SIST EN ISO 19157:2015. The analysis of the quality of the Real Property Register identifies key risks for violating the contemporary taxation system and the constitutional principles. The results of the analyses are supported with a cartographic representation for better perception and interpretation of the data quality. All municipalities% decrees with regard to the charge for the use of building ground as well as the data sources for the charge system management were studied. A multiple regression analysis was conducted to determine the influence of factors on the yield of the charge for the use of building ground. By the geographically weighted regression and the cartographic representation of the results the local properties of influence factors have been outlined. We developed our own methodological approach to analyse the problem of the discontinuity of base taxes for the same kind of property at neighbouring value zones borders and the zones of payment of charge for the use of building ground respectively.
Keywords: cartographic presentation; cartography; davek na nepremičnine; Disertacije; geodesy; geodezija; geografsko obtežena regresija; Geographically Weighted Regression; kakovost prostorskih podatkov; kartografija; kartografski prikaz; multipla regresija; Multiple Regression; nadomestilo za uporabo stavbnega zemljišča; Nepremičnine; Obdavčenje; property tax; Prostorski podatki; spatial data quality; the charge for the use of building ground; thesis; Uporabnost; Zbirke